2020
DOI: 10.1177/2192568220975375
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis With Use of Expandable Cage or Cement in Single level Thoracic Vertebrectomy in Metastasis

Abstract: Study Design: Retrospective case series. Objective: Patient with metastatic cancer frequently require spinal operations for neural decompression and stabilization, most commonly thoracic vertebrectomy with reconstruction. Objective of the study was to assess economic aspects associated with use of cement versus expandable cage in patients with single level thoracic metastatic disease. We also looked at the differences in the clinical, radiological, complications and survival differences to assess non-inferiori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…They will be used in a separate study to develop evidence-based recommendations for economic evaluations in spine surgery. Finally, a total of 130 clinical cost-effectiveness studies were included 24–153…”
Section: Resultsmentioning
confidence: 99%
“…They will be used in a separate study to develop evidence-based recommendations for economic evaluations in spine surgery. Finally, a total of 130 clinical cost-effectiveness studies were included 24–153…”
Section: Resultsmentioning
confidence: 99%
“…21,22 PMMA is most commonly used combined with Steinman pin augmentation, which results in a lower risk of dislodgment. In a recent cost analysis study, Katzir et al 23 found that PMMA reconstruction was associated with implant cost savings of approximately $20 thousand per vertebral body level and reduced overall operation Fig. 1…”
Section: Polymethylmethacrylatementioning
confidence: 99%
“…26 Additionally, expandable cages carry significantly higher implant costs compared with other reconstruction options such as PMMA. 23…”
Section: May 2022mentioning
confidence: 99%
See 1 more Smart Citation